La transposition profane de l’Exode dans Moïse fiction de Gilles Rozier - Sadkowski, Piotr (Quêtes littéraires, 2013)
Throughout the centuries French and Francophone writers were relatively rarely inspired by the figure of Moses and the story of Exodus. However, since the second half of 20th c. the interest of the writers in this Old Testament story has been on the rise: by rewriting it they examine the question of identity dilemmas of contemporary men. One of the examples of this trend is Moïse Fiction, the 2001 novel by the French writer of Jewish origin, Gilles Rozier, analysed in the present article. The hypertextual techniques, which result in the proximisation of the figure of Moses to the reality of the contemporary reader, constitute literary profanation, but at the same time help place Rozier’s text in the Jewish tradition, in the spirit of talmudism understood as an exchange of views, commentaries, versions and additions related to the Torah. It is how the novel, a new “midrash”, avoids the simple antinomy of the concepts of the sacred and the profane. Rozier’s Moses, conscious of his complex identity, is simultaneously a Jew and an Egyptian, and faces, like many contemporary Jewish writers, language dilemmas, which constitute one of the major motifs analysed in the present article. Another key question is the ethics of the prophetism of the novelistic Moses, who seems to speak for contemporary people, doomed to in the world perceived as chaos unsupervised by an absolute being. Rozier’s agnostic Moses is a prophet not of God (who does not appear in the novel), but of humanism understood as the confrontation of a human being with the absurdity of his or her own finiteness, which produces compassion for the other, with whom the fate of a mortal is shared.